Formation of Professional Competence of Future Law Specialists Under Globalization TransformationsУ статті розкрито вплив глобалізаційних процесів на формування професійної компетентності майбутніх юристів в умовах сучасної вищої освіти. Розглянуто понятт - Pei, Dong (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article reveals the impact of globalization processes on the formation of professional competence of future lawyers in the context of modern higher education. The concept of globalization, its social, cultural, and economic dimensions, and its significance for integrating national educational systems into the global educational space are examined. Globalization trends in the training of legal professionals and the role of international educational standards in ensuring the quality of education and the development of professional competencies are identified. It is emphasized that professionals in the legal field must possess not only deep theoretical knowledge of national law but also the ability to effectively apply international legal norms, work in multicultural environments, and participate in intergovernmental legal processes. The article analyzes methods for developing intercultural and communication competencies, including integrating foreign languages into academic disciplines, student participation in international internships, academic mobility programs, international scientific conferences, and the use of simulation exercises and roleplaying games. Key challenges include limited resources in higher education institutions, language barriers, and cultural differences that affect the effectiveness of competence development for legal professionals. The author emphasizes the need for a systematic approach to training future lawyers that combines theoretical education, practical skills, and intercultural competencies. It is stressed that integrating Ukrainian education into the international space, using innovative pedagogical technologies, developing academic mobility, and fostering international cooperation create the conditions for training highly qualified, competitive professionals capable of acting effectively in a globalized professional environment.